Hubungan Antara Self-Esteem Dengan Gangguan Emosional Pada Remaja SMA - Hendrianto, Rifat Adi; Istriana, Erita (Fakultas Kedokteran Universitas Trisakti, 2024)
Background Adolescents face numerous obstacles, including physical, emotional, and social changes that can have an impact on their self-esteem and mental health. Inability to deal with these difficulties can result in emotional disorders such as depression, anxiety disorders, and stress. Low self-esteem, or an individual’s image of oneself, is one of the elements that might precipitate the start of emotional disorders. The aim of this study is to determine the relationship between self-esteem and emotional disorders in adolescents at senior high school. Methods An observational analytic analysis with a cross-sectional design is used in this study. The study was carried out on SMAN 23 Jakarta students, and involved 131 respondens, which selected using consecutive random sampling methods. The RSES (Rosenberg Self-Esteem Scale) questionnaire was used to assess self-esteem, and the DASS-21 (Depression Anxiety Stress Scale) was used to examine emotional disorders. Results The study's findings were evaluated using the Pearson chi-square test, and no significant relationship was found between grade level and emotional disorders such as depression (p=0.691), anxiety (p=0.969) and stress (p=0.313). Furthermore, there was no significant relationship between body mass index and emotional disorders, such as depression (p=0.962), anxiety (p=0.257), and stress (p=0.975). However, a significant relationship was found between gender and emotional disorders, including depression (p=0.011), anxiety (p=0.000) and stress (p=0.009). Moreover, there was also a significant relationship between self-esteem and emotional disorders, including depression (p=0.002), anxiety (p=0.029), and stress (p=0.002). Conclusions This study found that there was no relationship between grade level, body mass index, and emotional disorders. However, a significant relationship was identified between gender, self-esteem, and emotional disorders among SMAN 23 Jakarta students.